GLOBAL VALUE CHAINS AND GEOPOLITICAL UNCERTAINTY disruption and transformation. (ROUTLEDGE, 2026)
This book offers a timely and insightful look at how political tensions, economic disruptions, and technological advances are reshaping the way goods and services move across borders. At a time when global trade faces mounting pressure, this book explores how businesses, governments, and communities can adapt to an increasingly uncertain world.Spanning diverse geographic areas and themes, the book delves into the evolving trade dynamics between developed and developing countries, the involvement of governments alongside international partnerships, as well as the impact of emerging digital technologies such as automation and artificial intelligence. Additionally, it addresses how companies are reevaluating their business models to enhance resilience, adopt sustainable practices, and meet rising demands for ethical conduct. Rich case studies from recent years bring these themes to life, highlighting real-world examples of innovation, adaptation, and strategic thinking.This volume serves as a vital resource for students, researchers, policymakers, and business executives aiming to comprehend and tackle the intricate challenges currently confronting global value chains. Whether engaged in international trade studies or overseeing a multinational enterprise, readers will find practical advice and forward-looking strategies essential for navigating a period characterized by transformation.